The Effect of Platelet PlA Polymorphism on Experimental Thrombus Formation in Man Depends on Blood Flow and Thrombogenic Substrate - Cadroy, Yves; Sakariassen, Kjell; Grandjean, Hélène; Thalamas, Claire; Boneu, Bernard; Sié, Pierre (Thrombosis and Haemostasis, 2001)
A number of studies have reported conflicting data on the association of the PlA1/PlA2 polymorphism of the GPIIIa gene and coronary syndromes. We have investigated the effect of this polymorphism on experimental platelet thrombus formation in man. Forty healthy male volunteers were genotyped for the PlA1/PlA2 polymorphism. Thrombus formation was induced ex vivo by exposing a tissue factor (TF) or a collagencoated coverslip in a parallel plate perfusion chamber to native blood for 2 and 4 min. The shear rates at these surfaces were 650 and 2,600 s–1. Platelet and fibrin deposition was quantified by immunoenzymatic methods. The frequencies of PlA1/PlA1 and PlA1/PlA2 genotypes were 52.5% and 47.5%, respectively. Ex vivo deposition of fibrin on TF was not affected by the PlA1/PlA2 polymorphism. However, the ex vivo platelet deposition at 650 s–1 was higher in blood from PlA1/PlA1 individuals than in PlA1/PlA2 individuals (P = 0.008 at 4 min). On collagen, neither fibrin nor platelet deposition was significantly affected by the PlA1/PlA2 polymorphism. Platelet thrombus formation is significantly influenced by genetic variations in the GPIIIa platelet receptor. This effect depends on the blood flow properties and the nature of the thrombogenic stimulus.
Keywords: Blood flow; genes; platelets; risk factors; thrombosis